Mapping and validation of Xanthomonas citri subsp citri genes regulated by putative plant-inducible promoter box (PIP-box) - Carvalho, F. M. S. [UNESP]; Oliveira, J. C. F. [UNESP]; Laia, M. L. [UNESP]; Jacob, T. R. [UNESP]; Ferreira, R. M. [UNESP]; Ferro, M. I. T. [UNESP]; Tezza, R. I. D. [UNESP]; Zingaretti, S. M. [UNESP]; Silva, C. F. [UNESP]; Ferro, J. A. [UNESP] (Funpec-editora, 2016)
Citrus canker, caused by the Gram-negative bacterium Xanthomonas citri subsp citri (Xac), is a major disease affecting citriculture worldwide, because of the susceptibility of the host and the lack of efficient control methods. Previous studies have reported that some genes of phytopathogenic bacteria possess a consensus nucleotide sequence (TTCGC...N15...TTCGC) designated the plant-inducible-promoter box (PIP box) located in the promoter region, which is responsible for activating the expression of pathogenicity and virulence factors when the pathogen is in contact with the host plant. In this study, we mapped and investigated the expression of 104 Xac genes associated with the PIP box sequences using a macroarray analysis. Xac gene expression was observed during in vitro (Xac grown for 12 or 20 h in XAM1 induction medium) or in vivo (bacteria grown in orange leaves for 3 to 5 days) infection conditions. Xac grown in non-induction NB liquid medium was used as the control. cDNA was isolated from bacteria grown under the different conditions and hybridized to the macroarray, and 32 genes differentially expressed during the infection period (in vitro or in vivo induction) were identified. The macroarray results were validated for some of the genes through semi-quantitative RT-PCR, and the functionality of the PIP box-containing promoter was demonstrated by activating beta-glucuronidase reporter gene activity by the PIP box-containing promoter region during Xac-citrus host interaction.
Keywords: PIP-Box promoter; Gene reporter beta-glucuronidase; Citrus canker; Xanthomonas citri; XAMI induction medium